MATHEMATICAL MODELING OF STRESS-STRAIN MODE OF VERTICAL STEEL CYLINDRICAL TANK WITH FLOPS ON AWALL - Паньків, Христина Василівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article the method of determining the stress-strain state of the vertical steel tanks wall’s material using its surface displacements is offered, which will in directly take into account all the loads that influence on the tank. Also, the method of the welded joints presence consideration is shown. Special attention is given to wall sections with flops form defects in which there are sign if cant displacement that are not caused by stress changes.